2012
DOI: 10.1016/j.schres.2011.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Distinct facial processing in schizophrenia and schizoaffective disorders

Abstract: Although schizophrenia and schizoaffective disorders have both similar and differing clinical features, it is not well understood whether similar or differing pathophysiological processes mediate patients’ cognitive functions. Using psychophysical methods, this study compared the performances of schizophrenia (SZ) patients, patients with schizoaffective disorder (SA), and a healthy control group in two face-related cognitive tasks: emotion discrimination, which tested perception of facial affect, and identity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 34 publications
5
14
0
1
Order By: Relevance
“…This slowness in reaching answers obviously affects daily life in persons with schizophrenia. The impaired performance of schizophrenia cases on both face memory and emotions domain were similar to other reports (Chen et al, 2012; Comparelli et al, 2013; Green et al, 2009; Kohler et al, 2010). …”
Section: Discussionsupporting
confidence: 90%
“…This slowness in reaching answers obviously affects daily life in persons with schizophrenia. The impaired performance of schizophrenia cases on both face memory and emotions domain were similar to other reports (Chen et al, 2012; Comparelli et al, 2013; Green et al, 2009; Kohler et al, 2010). …”
Section: Discussionsupporting
confidence: 90%
“…Tasks that assess true identity processing are primarily matching tasks, where the participant views static photographs of faces (with non-face identifying features removed, such as hair and spectacles), either serially or concurrently. The participant must match the identity of the first face to one of several options (Addington and Addington, 1998; Penn et al, 2000; Kucharska-Pietura et al, 2005; Chen et al, 2012). The most commonly used face-matching task is the Benton Test of Facial Recognition (Benton, 1983; see Figure 1A).…”
Section: Identity Processing Deficitsmentioning
confidence: 99%
“…One study using a booklet-based face-matching task with similar properties to the Benton also found no impairment (Hooker and Park, 2002). Three studies using a morphed identity-matching task—in which participants choose which of a pair of faces of varying similarity matches a briefly presented target—have also produced inconsistent results, with two studies reporting no impairment (Norton et al, 2009; Chen et al, 2012) and only one study approaching significance (Chen et al, 2009) (see Figure 1B). The reason for these inconsistent findings is unclear.…”
Section: Identity Processing Deficitsmentioning
confidence: 99%
“…Whether there is a correlation between face-processing deficits and clinical symptoms in patients with schizophrenia remains controversial. Some behavior studies have shown that neither positive nor negative symptoms are accompanied by face discrimination performance (Addington and Addington, 1998; Baudouin et al, 2002; Caharel et al, 2007), whereas other studies find significant correlations between negative symptoms and face recognition performance (Sachs et al, 2004; Martin et al, 2005; Norton et al, 2009; Chen et al, 2012), and one study found significant correlations between both positive and negative symptoms and face identity performance (Chen et al, 2009). Although many studies have examined the correlation between face-processing behavioral indices and schizophrenic symptoms, few have explored the correlation between face-processing electrophysiological indices and schizophrenia symptoms.…”
Section: Introductionmentioning
confidence: 98%